Interfaith Marriage Between Human Right and State Law - Dhiyaul Habib Ifham; Rosnidar Sembiring; Utary Maharani Barus (International Conference on Health Science, Green Economics, Educational Review and Technology, 2025)
Indonesia is not a religious country but Indonesia is also not a secular country, Indonesia does not make any religion the basis of the state, but all activities and behavior of Indonesian citizens cannot be related to religious matters. As this is supported by the first principle, namely "Belief in One Almighty God", this means that even though Indonesia is not a religious country, all behavioral norms of Indonesian citizens must not conflict with the norms of God. The polemic about interfaith marriages has been going on for a long time. Apart from the fact that there is a feeling of love between men and women, it is also because society in Indonesia is heterogeneous. Article 10 paragraph (2) of the Human Rights Law states that a valid marriage can only be carried out with the free will of both parties. This article contains the principle of the free will of the partner in the marriage bond. The meaning of free will is a will that is born on the basis of sincere, holy intentions without any coercion, deception or pressure. The Human Rights Law only looks at the civil aspect that there is no element of religion that takes precedence in a valid marriage bond. Article 28B paragraph (1) of the 1945 Constitution states "Everyone has the right to form a family and continue their offspring through legal marriage". Interfaith marriages carried out secretly are still valid according to those who carry them out, but as long as they live in Indonesia the marriage must be registered so that it is recognized by the state. On the other hand, how can interfaith marriages be considered valid when there are several religions that prohibit it, such as Islam, Protestant Christianity, etc. The presence of Law Number 1 of 1974 concerning Marriage cannot yet be convincing as a prohibition on Indonesian people wishing to carry out interfaith marriages, even though it is quite clear that Article 2 paragraph (1) states that "Marriage is valid if it is carried out according to the laws of each religion and belief. That". Then the Constitutional Court required that people who wanted to carry out interfaith marriages must ask permission from their respective religious leaders, so that the presence of religious leaders here greatly influences whether or not the interfaith marriage is valid. Not only that, some time ago, on July 17 2023, the Supreme Court issued SEMA Number 2 of 2023 concerning Instructions for Judges in Adjudicating Applications for Registration of Marriages Between People of Different Religions and Beliefs. The issuance of SEMA Number 2 of 2023 has a fundamental spirit to provide certainty and unity in the application of the law, so that there are no more loopholes for Indonesian people who wish to carry out interfaith marriages in Indonesia.